Relationship between pasture structure and utilization of tropical forage plants - Hodgson, John (International Center for Tropical Agriculture, 1993)
Variations in sward canopy structure can exert an important influence on the ingestive behavior of grazing animals and hence on herbage intake and utilization. In tropical swards, the structural characteristics of major importance appear to be total herbage density or leaf bulk density and leaf-to-stem ratio. However, there is a need for a closer examination of the associations between sward variables and animal responses if selection for structural characteristics is to be put on a sound footing. Factors contributing to an increase in intake will normally improve the efficiency of utilization. However, in some circumstances they may inhibit selective grazing activity or contribute to increased herbage losses. Identification of important structural variables requires detailed description of sward characteristics and animal responses. Once identified, initial screening for these variables should be accommodated within existing resources, but eventual selection for intake and utilization characteristics should be carried out under grazing conditions, particularly if mixed grass-legume swards are to be evaluated. The acceptable balances between grass and legume or between intake and feed reserves will be strongly influenced by the eventual application of the plant material under test.